Expressão da E-caderina em carcinoma de células escamosas e no tumor de células basais de cães - JOÃO, Carolina Franchi (2015)
The cadherins are a group of cellular adhesion molecules that are expressed on the surface of all epidermic layer. The E-cadherin is the main cadherin involved in epithelial cellular adhesion; the decrease in its expression is related to the progression of some types of cancer, to its metastatic characteristics, and to the prognosis, specially carcinomas. The squamous cell carcinoma and the basal cells tumors are a malignant epithelial neoplasm which affects dogs. The goal of this study was to evaluate E-cadherin's expression in canine tissues that were classified as squamous cell carcinoma or basal cell tumor, and to find a correlation with the biological behavior of the tumors. The squamous cell carcinomas showed significantly decreased expression of the molecule compared to the basal cell tumors when evaluated by Fisher's test (P=0.0039). Also, the more differentiated neoplastic cells had a higher intensity of color than the less differentiated ones. In conclusion, it is suggested that the reduced expression of E-cadherin in skin tumors may indicate greater power infiltrative and consequently poor prognosis in dogs.